Management of Tomographically Suspicious Fellow Eyes of Young Patients With Unilateral Clinically Evident Keratoconus: Accelerated Epithelium-On Corneal Crosslinking Versus Observation - Abdel-Radi, Mahmoud; Anwar, Mohamed; Aly, Momen Ahmad Mohammad; Eata, Wael El Shazly; Goda, Islam (Cornea, 2025)
To investigate the effectiveness and safety of accelerated epithelium-on crosslinking to stabilize tomographically suspicious fellow eyes of young patients with unilateral clinically evident keratoconus (KC) compared with observation alone. This retrospective observational study included 43 fellow eyes of 43 young patients with unilateral clinically evident KC who completed a 24-month follow-up. Twenty-four eyes underwent accelerated epithelium-on crosslinking [epi-on corneal crosslinking (CXL) group] and 19 eyes were observed (observation group). A third healthy control group was added for comparison. The primary outcome measures were tomographic parameters and topometric indices assessed by pentacam. Secondary outcome measures included corneal ectatic progression defined as 1-diopter or more increase in maximum or steep keratometry (K max or K 2 ), visual & refractive outcomes, and complications. Baseline demographic and tomographic characteristics were similar between the epi-on CXL and observation groups ( P > 0.05). Almost all mean tomographic parameters and topometric indices showed insignificant differences between baseline and after 24 months in the epi-on CXL and control groups ( P > 0.05), whereas a significant progression was documented in the observation group ( P < 0.05). At the end of the follow-up, progression was documented in 1 eye (4.2%) and in 8 eyes (42.1%) in the epi-on CXL and observation groups, respectively. Visual and refractive outcomes were more favorable in the epi-on CXL group. No significant complications were reported after accelerated epi-on CXL. Accelerated epithelium-on CXL was safe and achieved better tomographic stability and less corneal ectatic progression in tomographically suspicious fellow eyes of young patients with unilateral clinically evident keratoconus compared with observation alone.